Analyzing Speech Act Found in the EFL Class - Barnas, Adya (Universitas Swadaya Gunung Jati, 2015)
In teaching learning, lecturers teach the students with a good sentence. But there is one of students may not understand what she said although in grammatically is correct, so it will happen miscommunication between lecturer and student. This research concerns in the classroom interaction in Class I,J as the main data of this research because there are many speech acts especially categories of speech act employed by lecturer and students in the interaction related to the context and situation. This research belongs to descriptive qualitative research since it employs the analysis of descriptive and qualitative methods. The type of this research is descriptive qualitative. The participants of this classroom interaction are Mrs. Lutfhi as the lecturer and students from class I,J whereas the 6 men and 27 women. The topic is talking about social problem. In this case the writer analyzes the speech act found in the classroom interaction. The listener of this interaction ought to understand the meaning of the speaker.